Climate Change Increases Susceptibility to Grazers in a Foundation Seaweed - Kinnby, Alexandra; Toth, Gunilla B.; Pavia, Henrik (Frontiers in Marine Science, 2021)
Climate change leads to multiple effects caused by simultaneous shifts in several physical factors which will interact with species and ecosystems in complex ways. In marine systems the effects of climate change include altered salinity, increased temperature, and elevated pCO2 which are currently affecting and will continue to affect marine species and ecosystems. Seaweeds are primary producers and foundation species in coastal ecosystems, which are particularly vulnerable to climate change. The brown seaweed Fucus vesiculosus (bladderwrack) is an important foundation species in nearshore ecosystems throughout its natural range in the North Atlantic Ocean and the Baltic Sea. This study investigates how individual and interactive effects of temperature, salinity, and pCO2 affect F. vesiculosus, using a fully crossed experimental design. We assessed the effects on F. vesiculosus in terms of growth, biochemical composition (phlorotannin content, C:N ratio, and ∂13C), and susceptibility to the specialized grazer Littorina obtusata. We observed that elevated pCO2 had a positive effect on seaweed growth in ambient temperature, but not in elevated temperature, while growth increased in low salinity at ambient but not high temperature, regardless of pCO2-level. In parallel to the statistically significant, but relatively small, positive effects on F. vesiculosus growth, we found that the seaweeds became much more susceptible to grazing in elevated pCO2 and reduced salinity, regardless of temperature. Furthermore, the ability of the seaweeds to induce chemical defenses (phlorotannins) was strongly reduced by all the climate stressors. Seaweeds exposed to ambient conditions more than doubled their phlorotannin content in the presence of grazers, while seaweeds exposed to any single or combined stress conditions showed only minor increases in phlorotannin content, or none at all. Despite the minor positive effects on seaweed growth, the results of this study imply that climate change can strongly affect the ability of fucoid seaweeds to induce chemical defenses and increase their susceptibility to grazers. This will likely lead to widespread consequences under future climate conditions, considering the important role of F. vesiculosus and other fucoids in many coastal ecosystems.